The recent progress of peptide regulators for the Wnt/β-catenin signaling pathway - Zhang, Nan; Shen, Huaxing; Chen, Baobao; Hu, Honggang; Liu, Chao; Chen, Yan; Cong, Wei (Frontiers in Medicine, 2023)
Wnt signaling plays an important role in many biological processes, such as stem cell self-renewal, cell proliferation, migration and differentiation. The β-catenin–dependent signaling pathway mainly regulates cell proliferation, differentiation and migration. In the Wnt/β-catenin signaling pathway, the Wnt family ligands transduce signals through LRP5/6 and Frizzled receptors to the Wnt/β-catenin signaling cascades. Wnt-targeted therapy has garnered extensive attention. The most commonly used approach in targeted therapy is small-molecule regulators. However, it is difficult for small-molecule regulators to make great progress due to its inherent defects. Therapeutic peptide regulators targeting the Wnt signaling pathway have become an alternative therapy, promising to fill the gaps in clinical application of small-molecule regulators. In this review, we describe recent advances in peptide regulators for Wnt/β-catenin signaling.